Microvessel density and PSA level in prostatic adenocarcinoma of Gleason score 6 and 7: Gostota malih žil in vrednosti PSA pri adenokarcinomih prostate z oceno 6 in 7 po Gleasonu - Dariš, Barbara; Munda, Miha (Acta Medico-Biotechnica, 2021)
Purpose: The aim of this investigation was to determine the differences in microvessel density (MVD) and serum levels of prostate-specific antigen (PSA) between groups of patients with Gleason score (GS) 6 prostatic adenocarcinoma and patients with GS 7 prostatic adenocarcinoma. Methods: The study included a series of 100 patients with prostatic adenocarcinoma. Tumor specimens were divided into two groups: GS 6 (52 cases) and GS 7 (48 cases). Intratumoral microvasculature was determined by immunohistochemistry using an antibody against endoglin. Endoglin stained microvessels were observed in and around the tumor, but weak or no staining of blood vessels was seen in non-neoplastic tissue. Areas of maximal angiogenesis within the tumor were identified and microvessels were counted at ×400 magnification (0.19 mm2 field). Results: The GS 6 specimens did not significantly differ in MVD per field (24.5 vs. 29.0; P=0.46) or MVD per mm2 (109.3 vs. 129.6; P=0.78) when compared with the GS 7 specimens. No significant difference in mean serum levels of PSA between the two groups was observed (8.5 vs. 10.1 ng/mL; P=0.66). MVD per mm2 was not correlated with PSA (r=0.1; P=0.62). The age of patients at diagnosis was not significantly different between the two groups (63.0 vs. 65.0 years; P=0.84). Conclusion: Our results show no significant differences in neovascularization and PSA level between Gleason score 6 and 7 prostatic adenocarcinoma.